PEWARNA ALAMI BATIK DARI TANAMAN NILA (Indigofera) DENGAN KATALIS ASAM - Astuti Handayani, Prima; Amar Mualimin, A. (Jurnal Bahan Alam Terbarukan, 2013)
Indigo is a natural blue dye substance of batik extracted from the leaves of indigo plant, which is eco-friendly and non-carcinogenic. To be able to extract an indigo dye substance, the indican glycosides contained in the leaves of the plant is first hydrolyzed into Indigo indoxyl and glucose by using either the dilute mineral acids or enzymes. The indoxyl is then oxidized to indigo. In this experiment, the extraction of the blue dye substance of indigo plant was carried out by method of acidifying. The observations made on the variation of the concentration of hydrochloric acid, the aeration time, the acids, and the type of binding substances. The material used in the experiment included the 2 months old of Indigo leaves, hydrochloric acid, sulfuric acid, sodium hydroxide, sugar, lime, alum and tunjung (Ferrous sulfate). The equipments used in the aeration were beaker glass and the air pump.The process was initiated by soaking the indigo leaves in acid with a specific concentration for 24 hours. The filtrate was then oxidized by flowing the air using the air pump for 12 hours. Then, the sample was applied by immersing the fabric in a solution of the binding substances consisted of Ferrous sulfate, alum, and lime. The experiment results show that higher concentration of indigo was obtained from the longer aeration time. By comparing different type of acids, the extraction using 0.01 M H2SO4 shows better than using HCl in the same concentration. The highest indigo concentration produced by the extraction using 0.01 M H2SO4 was 29.20 ppm, while the highest concentration produced from the extraction using 0.01 M HCl was 26.88 ppm. The use of different type of binding substances on the fabric, giving the appearance of different colors. The binding substance of Tunjung produces the dark blue color, lime produces greenish blue colour, and alum produces a blue color.